Neural Activities in Multiple Rat Brain Regions in Lithium-Pilocarpine-Induced Status Epilepticus Model - Fan, Jingjing; Shan, Wei; Yang, Huajun; Zhu, Fei; Liu, Xiao; Wang, Qun (Frontiers in Molecular Neuroscience, 2020)
To compare the different regional brain EEG activities and biochemical responses between seizure and epilepsy models, we assessed the EEG and c-Fos immunolabeling characteristics in a lithium-pilocarpine-induced status epilepticus model and PTZ-induced seizure model. The regional brain activities were evaluated by EEG and c-Fos immunolabeling. ZnT3 immunostaining was performed to observe hippocampal mossy fiber sprouting within seven days after the induction of status epilepticus in the lithium-pilocarpine model. The EEG recordings showed distinctive features of activation in different brain areas. With the aggravation of the behavioral manifestations of the seizures, the frequency and amplitude of the discharges on EEG gradually increased. Status epilepticus was eventually induced and sustained. The labeling of c-Fos was enhanced in the cortex and hippocampal CA1, CA3, and dentate gyrus; however, compared to the PTZ-induced seizure model, c-Fos staining could only be observed in the striatum and thalamus in the lithium-pilocarpine-induced epilepsy model. In each brain region, prominent c-Fos labeling was observed 2 h and 4 h after the induction of status epilepticus or seizures and diminished at 24 h. During the lithium-pilocarpine-induced chronic epilepsy phase after SE induction, mossy fiber sprouting was observed seven days after SE and was accompanied by the dynamic evolution of epileptic EEG activities. These findings validated the lithium-pilocarpine-induced status epilepticus model as an epilepsy model with a specific spatial-temporal profile of neural activation. The EEG characteristics and c-Fos expression pattern differ from those presented in a previous study using a PTZ-induced seizure model. Hippocampal mossy fiber spouting might be associated with spontaneous seizures during the chronic phase and can be detected at least within one week by ZnT3 staining after stimulation.